Export credit agencies : the unsung giants of international trade and finance - Gianturco, Delio E., 1940- (Quorum Books, 2001)
Export credit agencies are specialized financial institutions that cover 1 trillion of exports each year. Their contribution to their nations' growth is significant. This book reveals and explains their history, role, functions and the controversies surrounding them.